Significance of Innovative Learning Skills in the Era of Education 4.0 - Mubarak, Zainab Khalfan; Selimin, Mohamad Ali (International Journal of Sustainable Construction Engineering and Technology, 2023)
Considering the rapidly evolving technological landscape, innovative learning skills have become indispensable for Education 4.0. Therefore, this paper presents a study aimed at assessing the level of importance and prioritization of innovative learning skills in the context of Education 4.0 among high school students in the UAE. The study utilized a questionnaire survey, distributing 150 questionnaire sets to selected high school students in Abu Dhabi, UAE. Subsequently, the collected data was subjected to statistical analysis using SPSS software. The analysis of data importance revealed noteworthy findings. Specifically, the skills TS1 ("I am familiar with online learning tools used in my school"), OCL1 ("I learn online collaboratively with my classmates"), and TSE1 ("I have confidence in my skills using technology") were identified as of very high importance for the requirements of Education 4.0 among UAE high school students. Regarding the ranking of innovative learning skill groups, the study unveiled that the Self-regulated learning (SRL) group attained the highest rank, boasting a mean score of 4.272. Following closely, the Technology Self-Efficacy (TSE) group secured a mean score of 4.248. In contrast, the Critical thinking skills (CTS) group ranked the lowest, garnering a mean score of 4.128. These rankings indicate that respondents perceive Self-regulated learning skills as the most proficient among the listed domains, while Critical thinking skills are perceived as the least proficient. The findings of this study have the potential to provide valuable insights to the educational community, aiding them in enhancing the skills necessary for Education 4.0.